Working IT Out in Medical Practice: IT Systems Design and Development as Co-Realisation - Hartswood, M. J.; Procter, R. N.; Rouchy, P.; Rouncefield, M.; Slack, R.; Voss, A. (Methods of Information in Medicine, 2003)
Objectives: The paper explores possibilities for situating IT design and development work within the context of use so as to support the co-realisation of technology and ‘design in use’. The aim is to build a new understanding between IT professionals and users which is grounded upon what happens as the latter grapple with the problems of applying IT, appropriating its functionalities and affordances into their work practices and relations.Methods: Following a discussion of participatory design and ethnomethodology, a novel method called co-realisation, which aims to provide a synthesis of the preceding methods, is suggested as an alternative. Through a discussion of findings from a case study of IT systems design and development in healthcare we show how the co-realisation approach might provide work-affording systems and how user-designer relations might be reformulated. We suggest that work-affording systems can be developed through the deployment of an engaged facilitator who works with the users to unpack the work site-specific potentialities of technology.Results: The case study shows how risk of non-adoption might be minimised through the development of partnerships, and how the presence of the facilitator in the workplace capitalises on the mundane work undertaken therein and how the facilitator might work with the users to develop artefacts that support this work as opposed to reconfiguring it.Conclusions: The case study illustrates co-realisation in action and how it might be seen to reconfigure relations between users and designers in a way that appears productive. Co-realisation can help address the widely observed problem of IT systems failures in healthcare.
Keywords: Ethnomethodology; IT systems design and development; participatory design; design in use